Geração concretista em São Paulo: uma biografia coletiva - Sandes, Luis Fernando Silva (2018)
This master’s dissertation examines the action of a group of fifteen artists and poets linked to the concrete art movement in Sao Paulo starting on the 1950s. The research problem refers to the constitution of the concrete art group and to its role on the modernization of the Brazilian artistic field. The research’s general objective is to understand how the affirmation of the concrete art generation in the city of Sao Paulo during the 1950s took place. There are three important theoretical and methodological tools: collective biography’s method and the concepts of generation from Mannheim and field from Bourdieu. These tools, the situation of the artistic field from that time, and the relation of the Brazilian concrete art movement to the constructive movement are discussed in the introduction. In the second chapter, the dissertation limits itself to the period from 1947 to 1959. During such time span, cultural institutions relevant to the appearance of concrete art movement have arisen. The concrete art movement emerged officially in 1952. Active as a group until 1959, it held debates with other artistic streams and took over relevant positions in the artistic field. Focusing this period of twelve years, the collective biography’s method is used. Such method prescribes extracting relevant social information from defined populations. The resulting collective biography shows a variety of topics, artistic or not strongholds, and exhibits, all in common to the fifteen selected people. In the following two chapters, concrete art movement in Sao Paulo is studied in its unfoldings. In the third chapter factors that have collaborated for the recovery of concrete art after its peak during the 1950s are raised. Among those factors are art collections, art galleries, libraries and book anthologies. In the fourth chapter the echoes of concrete art movement in the contemporaneity are investigated. It is studied how concrete art movement is still nowadays present in the artistic field, considering its artistic proposals and beyond. As a conclusion a group portrait is shown, in which commonalities of the studied population are specified and a interpretative viewpoint is done. The examined material is composed of biographies, manifestoes, autobiographical pieces of writing, exhibition catalogues, monographic studies on artists, articles and critiques published in newspapers, interviews to the author, among others